(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
This article will deal with the question of whether migrants from Asian and African countries are entitled to a compensation for the damage caused by a motor vehicle for which a compulsory insurance contract has not been concluded, from the assets of the guarantee fund. Migrants who were injured by the use of an uninsured vehicle in the Republic of Serbia addressed the Association of Serbian Insurers with a claim for damages. The Association of Serbian Insurers refused such requests on the grounds that the Serbian citizen in the country from which the migrant originated could not receive such compensation in the same case. By an inductive method the author will, proceeding from individual decisions of the Association of Insurers of Serbia answer the question whether migrants in the Republic of Serbia can receive compensation for damage from the assets of the guarantee fund. By the dogmatic method, the author will come to the conclusion that the positive regulations of the Republic of Serbia grant migrants the right to compensation from the guarantee fund, but only if there is a guarantee fund in the country from which the migrant comes from, from which a Serbian citizen could be compensated. The axiological method will be applied at assessing the value by the specified conditions. The comparative method will be used to clarify whether according to the regulations of other countries located on the so-called “the Balkan route”, migrants are entitled to receive compensation from the funds of the guarantee fund. The author will conclude that the countries, while adjusting to EU membership, should acknowledge migrants compensation for damages from the guarantee fund.